BIASES IN ENGLISH TRANSLATION OF CULTURAL WORDS IN AYU UTAMI'S SAMAN - Alfarren Syarian, - (2020)
In translation, no one can escape from biases including biases in translating cultural words. Bias in this context is any alteration done by the translator in order to provide the best translation as possible to the TL readers. This study analyzes how biases occurred in the English translation of Ayu Utami's Saman, one of Indonesia's influential contemporary novels. Using Ghazala's (2002) study on bias in translation and Newmark's (1988) study on cultural words as well as translation procedures, this study found biases in the translation of cultural words in terms of organization, customs, activities, procedures, concepts; social culture; material culture; ecology; gestures and habits. Most of the biases are considered positive in meanings for certain intentions. For the purpose of translations, the biases found in the novel are mostly acceptable and even required, while only a few of them are negative. These findings indicate that bias is unavoidable and in some cases necessary in translation process.